Two-dimensional signal transduction during the formation of invadopodia - Noor Azhuan, N. A. (Universiti Putra Malaysia, 2019)
Signal transduction is an important process associated with invadopodia formation which consequently leads to cancer cell invasion. In this study, a two-dimensional free boundary problem in a steady-case of signal trans- duction during the formation of invadopodia is investigated. The signal equation is represented by a Laplace equation with Dirichlet boundary condition. The plasma membrane is taken as zero level set function. The level set method is used to solve the complete model numerically. Our results showed that protrusions are developed on the membrane surface due to the presence of signal density inside the cell.